2021
DOI: 10.4103/picr.picr_122_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices of health-care providers toward antibiotic prescribing, antibiotic resistance, and multidrug-resistant tuberculosis

Abstract: Introduction: Antibiotic resistance (ABR) is a growing public health problem and is a subject of international concern. It poses a serious threat to health and health-care systems in both developed and developing countries. The problem is more confounding with tuberculosis (TB), and drug resistance in TB has threatened the progress made in TB care and control worldwide. The aim of this study was to understand the knowledge, attitude, and practices of health-care providers (HCPs) toward antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…A large number of practitioners (80.8%) admit to having encountered MDR-TB in their clinical practice and the majority (95.2%) of the health care practitioners (HCPs) believe MDR-TB is a rising problem. Another study also reported that antibacterial resistance in the treatment of TB is an important and increasing public health problem [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of practitioners (80.8%) admit to having encountered MDR-TB in their clinical practice and the majority (95.2%) of the health care practitioners (HCPs) believe MDR-TB is a rising problem. Another study also reported that antibacterial resistance in the treatment of TB is an important and increasing public health problem [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These knowledge gaps regarding MDR-TB were also identified by other studies. In one study, the authors reported that 59.2% of their study participants strongly agreed that the indiscriminate use of anti-TB drugs could be a major factor attributing to MDR-TB [ 9 ]. This could be due to the fact that most of the sensitization and training programs in our country are held in the government settings, but in a high burden country like India, the training programs should be robust and rigorous and should be conducted in every setting (both private and government) on a regular basis to achieve the ultimate goal of TB elimination by 2025 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perolehan pengkajian ini selaras pada Chan, dkk di Malaysia yang mengatakan bila "ibu yang memiliki tingkat pengetahuan dan sikap rendah, menunjukkan tingkat perilaku rendah juga" (15). Tindakan edukasi dan persuasif tentu saja diperlukan, tetapi penggunaan tindakan restriktif dan terorganisir tampaknya wajib dilakukan jika penyalahgunaan antibiotik ingin dikurangi dalam waktu dekat (19). Penting untuk memahami hubungan antara penggunaan antibiotik dan resistensi bakteri untuk membantu merumuskan kebijakan dan praktik penggunaan antibiotik yang lebih bijaksana (20).…”
Section: Pembahasanunclassified
“…22 Inappropriate antibiotic usage is influenced by various factors that contribute to the misuse and overuse of these medications in addition to one significant factor that is physicians’ nonadherence to treatment guidelines, which may stem from a lack of awareness or disregard for established protocols, so the nurse’s role is to adhere to the physician to follow the protocol. 23 Additionally, insufficient knowledge of MDROs (nurses) plays a role in this global problem. Fear of clinical failure and external pressures, such as influence from patient demands for antibiotics regardless of necessity, also contribute to the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Fear of clinical failure and external pressures, such as influence from patient demands for antibiotics regardless of necessity, also contribute to the problem. Furthermore, self-prescribing exacerbates the issue by bypassing professional medical guidance, and all of these challenges addressed by Malhotra et al 23 were found to contribute to antibiotic resistance. It is crucial to provide guidelines and timely, comprehensive information to address this concern and this needs an educational program.…”
Section: Introductionmentioning
confidence: 99%